APPROACHES BASED ON COMPLEXITY ARE INADEQUATE TO SOLVE THE MIND-BODY PROBLEM - Blanco, Carlos (THÉMATA. Revista de Filosofía, 2015)
This paper aims to offer a broad criticism of the underpinnings of the so-called “complexity-theories” in their approach to a problem that has puzzled philosophers and scientists for centuries: the relationship between mind and body. We will pay special attention to the ideas of Alicia Juarrero, a distinguished exponent of this explanatory model, whose epistemological implications will be outlined in regard to her diffuse understanding of causality. El artículo plantea una crítica general de los fundamentos subyacentes a las denominadas “teorías de la complejidad”, al menos en su tratamiento de un problema que ha desconcertado a filósofos y científicos a lo largo de los siglos: la relación entre la mente y el cuerpo. Presta especial atención a las ideas de Alicia Juarrero, exponente distinguida de este modelo explicativo, con el objetivo de discutir las implicaciones epistemológicas de su proyecto, sobre todo de su difusa comprensión de la causalidad.